A Structural Equation Modeling Analysis of Parental Factors Underlying the Demand for Private Supplementary Tutoring in China. (March 2019) - Liu, Junyan
Purpose: Private supplementary tutoring has been increasingly used by parents as part of wider strategies to assist their children's education careers in China. With a theoretical lens of parentocracy, this article aimed to investigate the influential parental factors underlying the demand for private tutoring, focusing on parents' socioeconomic resources and attitudes toward education. Design/Approach/Methods: This article drew upon data from the 2014 iteration of the China Family Panel Studies. Structural equation modeling (SEM) analysis was employed to explore the influences of parental factors. Findings: The SEM analysis confirmed that parental income, education, and aspirations on children's education had both direct and indirect positive effects through the mediating factor of role construction on demand for tutoring. A multiple-group analysis was further conducted, and the difference in the patterns for urban and rural parents was explored. Parental occupation had no impact on demand for tutoring for rural parents but had both direct and indirect effects for urban parents. Both direct and indirect effects of household income on demand for tutoring were greater for urban parents than for rural parents. Originality/Value: This article examined the direct and indirect influences of parental factors on demand for private tutoring and explored the differences in patterns for urban and rural parents in a quantitative way. Findings have implications for education inequality.